Prostate Cancer Incidence and Mortality Linked to Metalworking Fluid Exposure: A Systematic Review and Meta-Analysis - Moradpour, Zahra; Barik, Amin; Jorjani, Goljamal; Taherian, Mohammad Reza; Tousizadeh, Sepideh; Halimi, Aram; Soleimani, Yaser; Karimian, Mobina; Khavari, Tina; Azizi Kalankari, Fateme; et al. (Asian Pacific Journal of Environment and Cancer, 2024)
Introduction: Prostate cancer is a significant health concern, and occupational exposures, including metalworking fluid (MWF) exposure, have been implicated as potential risk factors. This protocol outlines a systematic review and meta-analysis methodology to investigate the association between MWF exposure and prostate cancer risk among male workers. Methods: Eligible studies include cohort, case-control, and cross-sectional studies published until between 1990 and 2023 focusing on MWF exposure and prostate cancer risk in male workers. Two independent reviewers will screen studies, extract data using a standardized form, conduct a meta-analysis using random-effects models, and assess study quality using the Newcastle-Ottawa Scale. Heterogeneity will be assessed, and sensitivity analyses will be conducted to explore sources of bias. Results: Anticipated outcomes include a comprehensive list of eligible studies, a synthesized analysis using random-effects meta-analysis models to estimate the association between MWF exposure and prostate cancer risk, and a quality assessment report of included studies. Subgroup analyses based on MWF type, exposure duration, and study design will be performed to explore heterogeneity. Conclusion: This systematic review and meta-analysis protocol aim to provide robust evidence on the association between MWF exposure and prostate cancer risk among male workers. The anticipated findings will have implications for occupational health practices and may guide future research and intervention strategies.